Impact Of Direct Cash Assistance On The Welfare Of The Community In Panrannuangku Sub-District North Polongbangkeng Takalar District - Muh. Yusuf Sulaiman (Pustaka Digital Indonesia, 2021)
The purpose of this study was to determine the impact of direct cash assistance on the welfare of the community in Panrannuangku Village, North Polongbangkeng District, Takalar Regency. This type of research is qualitative in nature whose data is obtained from informants. Sources of data used in data collection include primary data and secondary data. The research instrument used in this study used the interview method. observation and obtaining document data from the research site. The results showed that basically Direct Cash Assistance (BLT) can help the poor, but this program cannot improve the quality of life of the poor, let alone reduce the poverty rate, because this program is a short-term program and is temporary in nature.